Exploring the effects of SMEs' platform-based digital connectivity on firm performance – the moderating role of environmental turbulence. Issue 13 (9th January 2023) - Rajala, Anni; Hautala-Kankaanpää, Tuire
Abstract : Purpose: Small- and medium-sized enterprises (SMEs) often operate in environments marked by high levels of turbulence. Such firms adopt digital technologies and platforms that provide access to external real-time information and establish digital connectivity between firms to remain competitive. This study aims to focus on SMEs' downstream and upstream platform-based digital connectivity (PDC). Design/methodology/approach: This study examines the effects of PDC on SMEs' operational performance under conditions of environmental turbulence. The data was gathered from 192 SMEs operating in the manufacturing arena. Findings: The results show that the adoption of PDC does not directly affect an SME's operational performance. However, in highly turbulent environments, PDC can improve operational performance. The results indicate that the performance effects of PDC vary according to the level and type of environmental turbulence. Research limitations/implications: This research offers insights into the relationship between PDC among SMEs and operational performance and encourages future research examining other possible conditional effects that could explain the contradictory results found in previous research. Originality/value: This study contributes to the knowledge of supply-chain digitalization among SMEs and its performance effects in varying environmental conditions. Further, this study contributes to the prior research by focusing on the interorganizational aspects of digitalization in SMEs.